2018
DOI: 10.1152/ajpheart.00207.2018
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor antagonism improves parenchymal arteriole dilation via a TRPV4-dependent mechanism and prevents cognitive dysfunction in hypertension

Abstract: Hypertension and mineralocorticoid receptor activation cause cerebral parenchymal arteriole remodeling; this can limit cerebral perfusion and contribute to cognitive dysfunction. We utilized a mouse model of angiotensin II-induced hypertension to test the hypothesis that mineralocorticoid receptor activation impairs both TRPV4-mediated dilation of cerebral parenchymal arterioles and cognitive function. 16-18-week-old male C57bl/6 mice were treated with angiotensin II (800ng/kg/min) ± the mineralocorticoid rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 51 publications
5
37
0
2
Order By: Relevance
“…TRPV4 channel deletion did not change the generation of myogenic tone but resulted in a severe impairment in PA dilation suggesting a critical role for this channel in cerebral arteriolar dilation. This is consistent with previous studies in TRPV4 −/− mice and with our previous studies in C57BL/6 mice where inhibition of TRPV4 channels with the pharmacological antagonist GSK2193874 severely blunted PA dilation . Studies in the Nelson laboratory also showed that AngII hypertension alters the coupling of TRPV4 channels to the anchoring protein AKAP‐150 and that this impairs the channel activity and endothelium‐dependent dilation in mesenteric arteries .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…TRPV4 channel deletion did not change the generation of myogenic tone but resulted in a severe impairment in PA dilation suggesting a critical role for this channel in cerebral arteriolar dilation. This is consistent with previous studies in TRPV4 −/− mice and with our previous studies in C57BL/6 mice where inhibition of TRPV4 channels with the pharmacological antagonist GSK2193874 severely blunted PA dilation . Studies in the Nelson laboratory also showed that AngII hypertension alters the coupling of TRPV4 channels to the anchoring protein AKAP‐150 and that this impairs the channel activity and endothelium‐dependent dilation in mesenteric arteries .…”
Section: Discussionsupporting
confidence: 92%
“…That study suggests that TRPV4 channels play a minor role in L‐NAME– but not in AngII‐induced hypertension. However, TRPV4 channels play an important role in endothelial dysfunction in AngII hypertension …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations